PENGGUNAAN METODE INDEX CARD MATCH PADA MATA PELAJARAN IPS POKOK BAHASAN MENGENAL SEJARAH UANG - Sumayana, Yena (Mimbar Sekolah Dasar, 2015)
This research is a classroom action research with the shape of repeatedly the cycle. Subject of this research is the third year-students of a State Islamic Elementary School I, Bandung. Instrument used during this research is an essay test (viz. subjective test), namely test of every cycle and observation of students and teachers’ activity. Based on the research finding it is concluded that the learning process with the index card match method conducted in three cycles can enhance the students’ learning outcomes. The highest percentage of score average on the students’ activity is 90.30% at the third cycle. Meanwhile, the highest percentage of score average on the teachers’ activity is 94.10% at the third cycle. In addition, the students’ learning outcomes also increase at each of cycles. That is, the score average over the cycle I is 46.51%, of the cycle II 63.48%, and of the cycle III 78.48%.Keywords: index card match, method, learning outcome.